(untitled) (Research, Society and Development, 2021)
Violence against women is a major social and public health problem worldwide, considered a violation of human rights and causing damage to women’s physical and mental health. This article aims to describe the characteristics of cases of violence against female children and adolescents between 10 and 19 years old notified in the Northeast region of Brazil in the years 2015 to 2019. This is an ecological, descriptive, and quantitative study developed through the analysis of data available in SINAN, about the population residing in Northeast Brazil, in the years 2015 to 2019. The Microsoft Excel® version 2019 program was used for the organization and tabulation of data. 34,355 notifications of violence were registered in the years 2015 to 2019. There was a prevalence of notifications of women aged 15 to 19 years old, with 58.8% (n= 20,185) and of the brown color 65.4% (n= 22,463). Regarding education, there was a higher number of notifications from women with 5th to 8th grade incomplete Elementary School and incomplete High School, with 28.0% (n= 9,565). Given the findings, it points to the importance of the applicability of safety methodologies and prevention of violence suffered by women, and also, for the construction of effective public policies to combat violence against female children and adolescents, since they are in a state of vulnerability.